2013
DOI: 10.1021/ci300435j
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Target Predictions: Defining a Benchmarking Data Set and Comparison of Performance of the Multiclass Naïve Bayes and Parzen-Rosenblatt Window

Abstract: In this study, two probabilistic machine-learning algorithms were compared for in silico target prediction of bioactive molecules, namely the well-established Laplacian-modified Naïve Bayes classifier (NB) and the more recently introduced (to Cheminformatics) Parzen-Rosenblatt Window. Both classifiers were trained in conjunction with circular fingerprints on a large data set of bioactive compounds extracted from ChEMBL, covering 894 human protein targets with more than 155,000 ligand-protein pairs. This data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(165 citation statements)
references
References 44 publications
4
161
0
Order By: Relevance
“…In this regard, we applied the well established Laplacianmodified naive Bayesian classifier as implemented by Koutsoukas et al (44) and predicted potential targets of CIMO. It was found that membrane-associated phospholipase A2, histamine H2 receptor, proteinase-activated receptor 1, steroid hormone receptor ERR1, gonadotrophin-releasing hormone receptor, and prostaglandin E synthase had a normalized likelihood of 10.41, 4.98, 4.96, 4.43, 4.04, and 4.04 for CIMO, respectively.…”
Section: Cheminformatics-based Mode-of-action Rationalization For Cimmentioning
confidence: 99%
“…In this regard, we applied the well established Laplacianmodified naive Bayesian classifier as implemented by Koutsoukas et al (44) and predicted potential targets of CIMO. It was found that membrane-associated phospholipase A2, histamine H2 receptor, proteinase-activated receptor 1, steroid hormone receptor ERR1, gonadotrophin-releasing hormone receptor, and prostaglandin E synthase had a normalized likelihood of 10.41, 4.98, 4.96, 4.43, 4.04, and 4.04 for CIMO, respectively.…”
Section: Cheminformatics-based Mode-of-action Rationalization For Cimmentioning
confidence: 99%
“…44 We identified potential targets based on classspecific cut-offs and found different members the family of histone deacetylases (HDACs)…”
Section: In Silico Mode Of Action Analysis Of Ptb That Targets Hdac6mentioning
confidence: 99%
“…23 The predicted target, potassium voltage-gated channel subfamily A member 5, with a corresponding probability value of 0.069, is shown in Table 5. In addition, the occurrence of potassium voltage-gated channel subfamily A member 5 in the background dataset was measured.…”
Section: Cheminformaticsmentioning
confidence: 99%